Identification of suitable bread wheat (Triticum aestivum L.) lines for rainfed situation in Karnataka - Lohithaswa, H C; Biradar, S S; Naik, R V; Kalappanavar, I K; Patil, B N; Hanchinal, R R; Desai, S A (Journal of Cereal Research, 2011)
Karnataka is one of the important wheat growing states in the peninsular India. Most of the area is under rainfed condition dominated by durum wheat cultivation. In the recent years, the area under bread wheat is increasing under rainfed condition. This necessitated the identification of suitable lines for this situation. The success of any breeding programme depends upon the successful selection of genetically variable material in hand. To make the heritable improvement in characters, estimation of genetic parameters and genetic advance is required. Heritability estimates provides information about the extent to which a particular character can be transmitted to the successive generations. Knowledge of heritability of a trait guides a plant breeder to predict behavior of succeeding generations and helps in making desirable selections. Correlation studies along with path analysis provide a better understanding of the association of different characters with grain yield. Path coefficient analysis separates the direct effects from the indirect effects through other related characters by portioning the correlation coefficients (Dixet and Dubey, 1984). The present study was carried out to evaluate the genetic variability and inheritance of yield of some diverse lines for the development of desirable wheat genotypes for the rainfed areas.